2020
DOI: 10.1177/0973408220934649
|View full text |Cite
|
Sign up to set email alerts
|

Too Young to Know? A Multiple Case Study of Child-to-Parent Intergenerational Learning in Relation to Environmental Sustainability

Abstract: Little is known about child-to-parent intergenerational learning for environmental sustainability. This qualitative multiple case study research investigated how young Maltese children (aged three to seven years) influence their parents’ pro-environmental actions. Participants included 12 children and 10 parents. Data were collected via observations in one household and two state schools, conversational interviews with children, children’s drawings and their interpretations of them, children’s photograph inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Children's intra-and intergenerational influence must also be considered when estimating the practical significance of children's behavior changes. Findings of the present study contribute to the growing evidence base that children can be effective climate change communicators and change agents in their families and communities and across generations [11,12,35,[60][61][62][63][64]. A finding worth noting is that the largest single-item shift on the post-program survey was, "I talk to my friends and family about the environment" (see Table 3).…”
Section: Children's Climate Change Action: Multi-level Benefitsmentioning
confidence: 50%
“…Children's intra-and intergenerational influence must also be considered when estimating the practical significance of children's behavior changes. Findings of the present study contribute to the growing evidence base that children can be effective climate change communicators and change agents in their families and communities and across generations [11,12,35,[60][61][62][63][64]. A finding worth noting is that the largest single-item shift on the post-program survey was, "I talk to my friends and family about the environment" (see Table 3).…”
Section: Children's Climate Change Action: Multi-level Benefitsmentioning
confidence: 50%
“…Children are proven to have an influence on their parents' spending patterns and the immense commercial media environment that surrounds them (Calvert, 2008). Studies on children's environmental education have also demonstrated that children can influence the behaviours of their parents regarding sustainability issues (Spiteri, 2020), including sustainable consumption (Ritch & Brownlie, 2016). Despite all these promising signs, sustainability marketing and children are considerably under‐researched.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 99%
“…Nature-based education, including a wide range of approaches such as forest schools, nature kindergartens, outdoor education, environmental education, and sustainability education, has attracted considerable attention, both scholarly. This kind of education has overarching aims to support children through individual experiences (Beery & Jørgensen, 2016), cooperation (Gruno & Gibbons, 2020), collaboration (Spiteri, 2020), communication (Collado et al, 2020), exploration (Silverman & Corneau, 2017), construction (Dennis et al, 2014), and imagination (Cordiano et al, 2019). In addition, there are a variety of activities that can take place in naturebased education, such as using outdoor spaces as learning places (Leea & Bailie, 2019) and including nature as a resource or concept in the regular program (Harwood et al, 2020) in order to raise environmental awareness (Bonnett, 2021), create a bond between nature and children (Gull et al, 2019), protect the environment (Güler Yıldız et al, 2021), or learn with nature even during Covid-19 pandemic (Burke et al, 2021).…”
Section: Nature-based Learning For Young Childrenmentioning
confidence: 99%
“…Orman okulları, doğa anaokulları, açık hava eğitimi, çevre eğitimi ve sürdürülebilirlik eğitimi gibi çok çeşitli yaklaşımları içeren doğa temelli eğitim bilimsel olarak büyük ilgi görmüştür. Böyle bir eğitim, çocukları bireysel deneyimler (Beery & Jørgensen, 2016), işbirliği (Gruno & Gibbons, 2020;Spiteri, 2020), iletişim (Collado et. Al, 2020), keşif (Silverman & Corneau, 2017), inşa (Dennis ve diğerleri, 2014) ve hayal gücü (Cordiano ve diğerleri, 2019) yoluyla desteklemeyi kapsamaktadır.…”
Section: Geni̇şleti̇lmi̇ş öZetunclassified